Anthropological Perspectives on Epilepsy: Exploring Cultural Beliefs and Treatment Practices in Karagwe and Kyerwa Districts, Kagera, Tanzania - Ruhinda, Straton (Tanzania Journal of Sociology, 2025)
This study investigates the cultural beliefs, perceived causes, and treatment practices associated with epilepsy in Karagwe and Kyerwa districts of Kagera Region, Tanzania, through an anthropological lens. Using a qualitative case study design, the research explores how traditional and biomedical systems interact in shaping health-seeking behaviors and treatment outcomes among people with epilepsy (PWE). Data were collected through in-depth interviews with PWE, caregivers, biomedical practitioners, and traditional healers, selected via purposive sampling. Thematic analysis revealed that while biomedical practitioners frame epilepsy as a neurological disorder treatable with anti-epileptic drugs, access to consistent care is hindered by structural limitations such as high costs, drug shortages, and inadequate follow-up. Conversely, traditional healers interpret epilepsy through spiritual and cultural frameworks, attributing it to causes like witchcraft, curses, and ancestral displeasure. Many patients reported turning to traditional medicine due to dissatisfaction with biomedical outcomes, often guided by family and community influence. The findings highlight widespread medical pluralism, whereby patients move between systems based on perceived efficacy, cultural resonance, and social advice. This study underscores the importance of integrating biomedical and traditional health systems through culturally sensitive, collaborative approaches that respect indigenous knowledge while ensuring evidence-based care. It contributes to the broader discourse on epilepsy management in rural African settings and calls for health models that are both inclusive and contextually grounded.